Legal Review of the Social Significance of Indonesian Foundations in the Field of Health - Rusnidar Safitri (Jurnal Pembaharuan Hukum, 2025)
Based on the legal dynamics in Indonesia, this review examines the social significance of foundations operating in the health sector, with a focus on hospital foundations. The objective is to analyze the alignment between their legal framework, particularly Law Number 16 of 2001 on Foundations and Law Number 28 of 2004 on Health, and their intended non-profit, philanthropic missions. Employing a normative legal research method, the study analyzes primary legal materials, including legislation, and secondary sources such as scholarly opinions. The findings reveal a tension between the social mandates of foundations and their practical operations, where some entities engage in commercial activities or provide high-cost services, contradicting their stated social functions. Regarding taxation, hospital foundations without profit-seeking objectives and using all income for social activities can be exempt from income tax. The conclusion underscores that hospital foundations play a crucial social role in providing equitable health services, community development, and charitable activities, but require clearer regulations and consistent enforcement to prevent mission drift and ensure their contributions to public health welfare are fully realized.